2012
DOI: 10.1016/j.mce.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for the involvement of prostaglandin receptor EP4b in ovulation of the medaka, Oryzias latipes

Abstract: A cDNA for a prostaglandin E 2 (PGE 2 ) receptor subtype 4, EP4b (Ptger4b), was cloned from the medaka ovary. The effect of PGE 2 was examined using COS-7 cells expressing the recombinant Ptger4b protein. An increase in intracellular cAMP levels was observed when the cells were incubated with PGE 2 , but the increase in cAMP levels was nullified by the addition of the EP4 antagonist GW627368X. The expression of ptger4b mRNA was drastically induced by the addition of pregnant mare serum gonadotropin to the in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…On the other hand, the present study showed one of the PGs receptors, Ptger4, was markedly up-regulated prior to ovulation in both mouse and zebrafish data sets. It has already been shown that Pgr directly regulates ptger4 in the preovulatory follicles of medaka (Fujimori et al, 2012; Hagiwara et al, 2014). In contrast, the role of PTGER4 in ovulation has been overlooked in mammals as studies have focused more on the role of PTGER2 in COC expansion and ovulation (Harris et al, 2011; Kim SO et al, 2014; Trau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the present study showed one of the PGs receptors, Ptger4, was markedly up-regulated prior to ovulation in both mouse and zebrafish data sets. It has already been shown that Pgr directly regulates ptger4 in the preovulatory follicles of medaka (Fujimori et al, 2012; Hagiwara et al, 2014). In contrast, the role of PTGER4 in ovulation has been overlooked in mammals as studies have focused more on the role of PTGER2 in COC expansion and ovulation (Harris et al, 2011; Kim SO et al, 2014; Trau et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was performed using an Applied Biosystems 7300 Real-Time PCR System (Life technologies Inc., Rockville, MD). The PCR mixture preparation, PCR, and data analysis were carried out according to the previously reported protocol [68], [74]. To normalize the transcript levels of gonadotropin subunits (pituitary), gonadotropin receptors, metalloproteinases and their inhibitor (ovarian follicles), we tested the housekeeping genes cytoplasmic actin ( actb ), 18S rRNA ( rn18s1 ) and ribosomal protein L7 ( rpl7 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the expression of many proteins which associated with oxidative stress was changed in the germ cells after treatments with Bap and DBP and may associate with their reproductive toxicology. PKA C-beta and tubulin beta-5, which would be associated with germ cell structure, meiosis process and male fertility (Burton et al, 2006;Fujimori et al, 2012), were up-regulated after treatment with Bap. HnRNP DL, which acted as a transcriptional regulator and was associated with cell cycle (Akagi et al, 2000), also varied when exposed to Bap.…”
Section: The Changes In Total Protein Expressionmentioning
confidence: 98%